Stapedectomy as an outpatient procedure - (:unkn) unknown (My University, 1989)
Many ENT surgeons are accustomed to perform stapedectomy in a hospital setting. We present our results with 19 patients on whom stapedectomies were performed in an outpatient setting. In respect of hearing gain and complications, our results are not significantly different from the results of those series of stapedectomies performed in hospital. Thus, we believe that stapedectomy can be performed as an outpatient procedure.
Keywords: Adult; Female; Humans; Middle Aged; Male; Audiometry; Ambulatory Surgical Procedures; Ossicular Prosthesis; Stapes Surgery